Cellophane / biodegradable resin laminated film
The laminated film structure with a cellophane layer, inorganic oxide deposition, and biodegradable resin layer addresses transparency, biodegradability, and processability issues, ensuring high biodegradability and oxygen barrier properties.
Patent Information
- Application Number
- JP2023175362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
Existing transparent barrier films face challenges in achieving high biodegradability, transparency, and processability while maintaining sufficient seal strength and oxygen barrier properties, as they often suffer from issues such as reduced transparency due to light scattering, slow biodegradation, cracking, and unintended breakage during processing.
A laminated film structure comprising a cellophane layer with a specific softener content, a transparent deposition layer of inorganic oxide, and a biodegradable resin layer of polybutylene succinate or polybutylene succinate adipate, with the deposition layer between the cellophane and resin layers, ensuring a total light transmittance of 80% or more and an oxygen barrier property of 4 cc/m²·atm or less.
The laminated film achieves high biodegradability in soil and ocean environments, maintains transparency, and prevents unintended breakage during processing, while providing excellent oxygen barrier properties and sufficient seal strength.
Smart Images

Figure 2025065866000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent and biodegradable barrier film for packaging. [Background technology]
[0002] Transparent barrier films that can be heat-sealed are used as packaging materials for various products. Such packaging materials are often discarded after consumers purchase and open the products, making efficient collection difficult. Therefore, it is desirable to use materials that have biodegradability and have a low environmental impact. As such a material, cellophane is desirable because it is transparent and derived from cellulose, so it has a low environmental impact, but it has a problem that it cannot be heat-sealed by itself. As a countermeasure, a polyolefin film is sometimes laminated onto the sealant, but in order to save resources, cellophane that has gas barrier properties against oxygen and water vapor and can be heat-sealed by coating it with a thin polyvinylidene chloride (PVDC) resin is used. However, since PVDC is not biodegradable, a material that is more biodegradable while maintaining transparency and gas barrier properties is desired, and various materials and combinations of them are being considered.
[0003] Patent Document 1 proposes a biodegradable multilayer film with oxygen barrier properties, which is produced by laminating biodegradable resins such as polyhydroxycarboxylate copolymers and polycaprolactone on both sides of transparent cellophane and then depositing a transparent inorganic oxide thereon.
[0004] Patent Document 2 proposes a biodegradable film laminate having barrier properties against oxygen and water vapor, in which a transparent inorganic thin film layer is laminated by vapor-depositing silicon oxide, aluminum oxide, or the like onto a film of a biodegradable resin such as polylactic acid via a polylactic acid-based anchor agent.
[0005] Furthermore, Patent Document 3 proposes a gas barrier substrate film in which a transparent vapor-deposited thin film layer is formed on a biodegradable resin film such as a polysaccharide, a polypeptide, polylactic acid, polybutylene succinate (PBS), or polyethylene succinate, and a protective layer is further formed on top of the layer.
[0006] Furthermore, Patent Document 4 proposes a technique in which a transparent thin film of an inorganic metal compound is provided on one or both sides of a transparent flexible film such as cellophane, and then laminated with a heat-sealable polyethylene or polyolefin film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2002-178456 A [Patent Document 2] JP 2003-62923 A [Patent Document 3] JP 2006-199013 A [Patent Document 4] Jpn. Jpn. Published No. 52-024608 Summary of the Invention [Problem to be solved by the invention]
[0008] However, when a biodegradable resin with low transparency is laminated on both sides of cellophane, as in the multilayer film described in Patent Document 1, or when it is difficult to finish the resin surface smoothly and the number of interfaces increases, the transparency is impaired because light is easily scattered. On the other hand, when an attempt is made to make the resin layer thin in order to ensure transparency, it becomes difficult to achieve the seal strength required for general packaging bags.
[0009] In addition, although the polylactic acid used in the film laminate described in Patent Document 2 can ensure transparency, it is known that its biodegradation rate at room temperature is extremely slow and that it hardly biodegrades in normal soil, making it difficult to use in situations where high biodegradability is required.
[0010] In the laminate film described in Patent Document 3, when attempting to use PBS or the like, which has a high biodegradability, for the substrate film, the deposited thin film layer laminated on the substrate is prone to cracking during use, even if a protective layer is provided to prevent cracking of the deposited thin film layer, because the substrate itself is soft, and the barrier property is reduced.
[0011] The general cellophane used in the laminated film described in Patent Document 4 contains 10 to 15% by mass of a softener, but the moisture content decreases in the vacuum chamber during deposition processing, making the film itself weak and causing frequent unintentional cuts, making it difficult to process as a packaging material. Furthermore, non-biodegradable polyethylene and polyolefin-based films were laminated as heat-sealable films.
[0012] Therefore, an object of the present invention is to provide a transparent barrier film for packaging that achieves the required processability while maintaining a high biodegradation rate of the constituent materials. [Means for solving the problem]
[0013] The present invention relates to a cellophane layer having a content of a softener made of polyhydric alcohol of 16% by mass or more and 25% by mass or less; A transparent deposition layer made of an inorganic oxide; and a biodegradable resin layer made of polybutylene succinate, polybutylene succinate adipate, or a mixture thereof; The above problem was solved by providing a laminated film having a total light transmittance of 80% or more, in which the transparent vapor deposition layer is disposed between the cellophane layer and the biodegradable resin layer.
[0014] In addition to the above-mentioned constitution, the laminated film according to the present invention has an oxygen barrier property (OTR) of the transparent deposition layer of 4 cc / m 2 A form of 0.1 d atm or less can be adopted.
[0015] In addition to the above configuration, the laminated film according to the present invention can employ a configuration in which the thickness of the biodegradable resin layer is 10 μm or more and 50 μm or less. Effect of the Invention
[0016] The laminated film of the present invention has an extremely thin deposition layer and is made of cellophane and polybutylene succinate or polybutylene succinate adipate, both of which are highly biodegradable materials, so it is easily biodegradable in soil at room temperature and in the ocean, where there are even fewer microorganisms than in soil. This allows for practical biodegradability compared to films based on polylactic acid, which requires high-temperature compost conditions for decomposition.
[0017] Furthermore, the laminated film of the present invention uses a cellophane layer containing a softener made of polyhydric alcohols at a sufficiently high content compared to ordinary cellophane, so that unintended breakage of the cellophane layer, which has been a problem in materials to be vapor-deposited, is significantly suppressed. This is because cellophane has the property that, when the moisture content decreases, its tensile strength and tensile elongation decrease, making it hard and brittle. Softeners made of polyhydric alcohols have a higher boiling point than water and are less likely to evaporate, and when a sufficient amount is contained, they act to easily retain moisture in the cellophane and maintain its mechanical strength. This makes it difficult for unintended breakage to occur even in an environment such as a vacuum chamber where vapor deposition processing is performed, and allows stable processing.
[0018] The transparent deposition layer made of a metal oxide has high transparency, and even if it is formed between a cellophane layer and a biodegradable resin layer, the transparency of the laminate film as a whole can be ensured. Even if a biodegradable resin that is difficult to finish to a smooth surface is used for the biodegradable resin layer, the number of the biodegradable resin layers can be minimized to prevent a decrease in the transparency of the laminate film as a whole. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view showing an embodiment corresponding to the laminated film of Example 1 according to the present invention. [Diagram 2] FIG. 5 is a cross-sectional view showing an embodiment corresponding to the laminated film of Example 5 according to the present invention. [Diagram 3] FIG. 13 is a cross-sectional view showing an embodiment corresponding to the laminated film of Example 7 according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below with reference to embodiments. The present invention relates to a laminated barrier film that exhibits transparency and biodegradability.
[0021] A cross-sectional view of a basic embodiment of a laminate film according to the present invention is shown in Fig. 1. A laminate film 10 according to the present invention has at least a cellophane layer 11, a transparent vapor deposition layer 12, and a biodegradable resin layer 13, with the transparent vapor deposition layer 12 between the cellophane layer 11 and the biodegradable resin layer 13.
[0022] The cellophane layer 11 is made of cellophane containing a softener. As the softener, polyhydric alcohols such as glycerin and triethylene glycol can be used. The action of the hydroxyl groups of polyhydric alcohols contributes to the moisture retention and improves the softness of the film. The content of this softener must be 16% by mass or more, and is preferably 18% by mass or more. The softener content of typical cellophane is about 10 to 15% by mass, but at such a low content, the moisture content is too low when forming the next transparent deposition layer 12, making the cellophane brittle and causing frequent unintended breakage. By setting the content of the softener to 16% by mass or more, processing stability can be ensured when forming the transparent deposition layer 12 described later. On the other hand, the content of the softener must be 25% by mass or less, and is preferably 24% by mass or less. If it exceeds 25% by mass, the cellophane becomes too sticky and bleeds out, which may reduce adhesion.
[0023] The thickness of the cellophane layer 11 is preferably 12 μm or more, and more preferably 15 μm or more. If it is less than 12 μm, it is too thin, which makes it difficult to handle during film formation, and there is a high possibility that sufficient durability will not be ensured even if it is laminated with other layers. On the other hand, the thickness of the cellophane layer 11 is preferably 50 μm or less, and more preferably 45 μm or less. If it exceeds 50 μm, it is too thick, which slows down the film formation speed, resulting in poor production efficiency, and there is a high possibility that impregnation with chemicals and washing with water, etc., during film formation will be insufficient.
[0024] The transparent deposition layer 12 is formed by depositing an inorganic oxide on the cellophane layer 11 or on the first anchor coat layer 21 applied to the cellophane layer 11. If it is to be formed on the side of the biodegradable resin layer 13 described later, the biodegradable resin layer 13 is too soft and the transparent deposition layer 12 is easily cracked, and a separate protective layer must be provided to prevent damage. In contrast, if it is formed on the cellophane layer 11 or on the first anchor coat layer 21 applied to the cellophane layer 11, the cellophane layer 11 itself is less likely to deform than the biodegradable resin layer 13 and hardly stretches, making it easier to handle during transparent deposition, and facilitating the production of the laminated film 10. Furthermore, the biodegradable resin layer 13 formed thereafter also acts as a protective layer for the transparent deposition layer 12, preventing damage after production, and improving the durability of the laminated film 10.
[0025] By providing the transparent deposition layer 12, the laminate film 10 can exhibit excellent oxygen barrier properties while maintaining transparency. The oxygen barrier properties (OTR) of the laminate film 10 achieved by providing the transparent deposition layer 12 is 4.0 cc / m 2 d atm or less, and 3.0cc / m 2 4.0cc / m d atm or less is more preferable. 2 If the barrier property is so low that it exceeds 1000 d atm, problems may occur as a packaging material. The lower the OTR value, that is, the higher the barrier property, is preferable, and the higher the barrier property is, the more preferable it is when the OTR value is below the detection limit. The thickness of the transparent deposition layer 12 of such a laminated film 10 varies depending on the required OTR and transparency level, or the deposition material used, but when the inorganic oxide is aluminum oxide, it is preferably in the range of 3 nm to 20 nm, and more preferably in the range of 5 nm to 10 nm. When the inorganic oxide is silicon oxide, it is preferably in the range of about 10 nm to 200 nm, and more preferably in the range of 20 nm to 100 nm. If the thickness is too thin, the desired OTR cannot be obtained, and if the thickness is too thick, the coloring becomes strong, the transparency decreases, and defects such as cracks are easily generated in the transparent deposition layer 12.
[0026] As the inorganic oxide used for the transparent deposition layer 12, oxides with high transparency such as aluminum oxide and silicon oxide are preferable. Even if the transparent deposition layer 12 made of these is interposed, suitable transparency can be ensured for the laminated film 10 as a whole. The method for depositing these is not particularly limited, and a general method such as a vacuum deposition method, a sputtering method, or a chemical vapor deposition (CVD) method may be appropriately selected.
[0027] The biodegradable resin layer 13 may be polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), or a mixture thereof, or may be a mixture of these resins, such as polybutylene adipate terephthalate (PBAT) or 3-hydroxybutyrate-3-hydroxyhexanoate copolymer (PHBH). By laminating these biodegradable resins, it is possible to impart heat sealability while maintaining high biodegradability. As a lamination method, a method may be used in which the transparent deposition layer 12 is formed directly on the cellophane layer 11 or indirectly via another layer therebetween, and then the biodegradable resin is extrusion laminated or dry laminated on the surface of the transparent deposition layer 12 opposite the cellophane layer 11, but is not particularly limited thereto as long as the required thickness and surface smoothness can be achieved.
[0028] The thickness of the biodegradable resin layer 13 is preferably 10 μm or more, and more preferably 15 μm or more. If it is less than 10 μm, it is too thin, and the heat sealability is insufficient, that is, the seal strength cannot be made 6 N / 15 mm or more, or the protective effect of the transparent vapor deposition layer 12 becomes insufficient, making it difficult to manufacture while maintaining the required quality. On the other hand, there is not much advantage to making it too thick, and since the biodegradable resin layer 13 is soft, even if it becomes thick, the disadvantage in terms of handling is small, but the disadvantage in terms of cost cannot be ignored, so it is preferable that it is 50 μm or less. In addition, some biodegradable resins are difficult to finish to a smooth surface and have low transparency, so it is preferable to make it a single layer in order not to increase the number of interfaces of the biodegradable resin.
[0029] The cellophane layer 11, the transparent vapor deposition layer 12, and the biodegradable resin layer 13 may be in direct contact with each other, or an intermediate layer may be provided between them to further protect the transparent vapor deposition layer 12 from cracking, to improve the adhesive strength of each layer, and to impart additional properties. Cross-sectional views of laminated films 10a and 10b having such intermediate layers according to embodiments of the present invention are shown in Figures 2 and 3.
[0030] The first anchor coat layer 21 is formed on one surface of the cellophane layer 11, and when the transparent deposition layer 12 is formed thereon, the adhesive strength of the transparent deposition layer 12 is improved, and the integrity of the laminated film is improved, and the stability during production and the strength after production can also be improved. Examples of resins used in the first anchor coat layer 21 include polyester resins, urethane resins, polyol resins, and acrylic resins. In addition, isocyanate compounds, epoxy compounds, carbodiimide compounds, and the like can also be used as hardeners. These may be either solutions or suspensions in water or organic solvents, and may be either one-liquid types in which the hardener is mixed in advance or two-liquid types that are mixed before use. It is preferable that the coating amount of the first anchor coat layer 21 is within a range that does not impair the transparency of the laminated films 10a and 10b. Specifically, it is 0.01 g / m 2 More than 1.5g / m 2 If the thickness is too thin, the effect of improving the adhesive strength may not be fully exhibited, whereas if the thickness is too thick, the biodegradability of the laminated films 10a and 10b decreases accordingly.
[0031] The topcoat layer 22 protects the surface of the transparent deposition layer 12 after it is formed. By forming the topcoat layer 22 directly on the transparent deposition layer 12, it is possible to prevent the transparent deposition layer 12 from cracking when it is bent by a machine such as a printer while being in contact with a roll or the like. Examples of resins used for the topcoat layer 22 include polyester resins, urethane resins, polyol resins, and acrylic resins. In addition, isocyanate compounds, epoxy compounds, carbodiimide compounds, and the like can also be used as hardeners. These may be either a solution or a suspension in water or an organic solvent, and may be either a one-liquid type in which a hardener is mixed in advance, or a two-liquid type in which the hardener is mixed before use. In order to maintain the biodegradability rate of the laminated film 10b, it is desirable to use a biodegradable material for the topcoat layer 22 as well. The presence of the topcoat layer 22 also exhibits the effect of improving the oxygen barrier property. The coating amount of the topcoat layer 22 is 0.05 g / m 2 More than 2g / m 2 It is preferable that the content is not more than 100%. If the content is too high, the protective effect of the transparent vapor deposition layer 12 is not improved, the manufacturing cost increases, and the decrease in transparency becomes significant. If the content is too low, the transparent vapor deposition layer 12 cannot be protected, and the effect of improving the barrier property is also reduced.
[0032] The second anchor coat layer 23 is formed on the surface of the transparent deposition layer 12 or on the top coat layer 22 formed thereon, and improves the adhesion with the biodegradable resin layer 13 formed thereon, thereby improving the integrity of the laminated films 10a, 10b, as well as the stability during production and the strength after production. Examples of resins used in the second anchor coat layer 23 include polyethyleneimine resins, organic titanium resins such as alkyl titanates, butadiene resins, polyester resins, polyurethane resins, polyol resins, and acrylic resins. In addition, isocyanate compounds, epoxy compounds, carbodiimide compounds, and the like can also be used as hardeners. These may be either solutions or suspensions in water or organic solvents, and may be either one-liquid types in which the hardener is mixed in advance or two-liquid types that are mixed before use. It is preferable that the coating amount of the second anchor coat layer 23 is within a range that does not impair the transparency of the laminated films 10a, 10b. Specifically, it is preferable that the coating amount of the second anchor coat layer 23 is within a range that does not impair the transparency of the laminated films 10a, 10b. 2 More than 1.5g / m 2 If the thickness is too thin, the effect of improving the adhesive strength may not be fully exhibited, whereas if the thickness is too thick, the biodegradability of the laminated films 10a and 10b decreases accordingly.
[0033] The method for providing the first anchor coat layer 21, the top coat layer 22, and the second anchor coat layer 23 is not particularly limited, and they can be formed by general methods such as gravure coating, reverse coating, and die coating.
[0034] Furthermore, when a printed layer is formed, it is possible to protect not only the transparent vapor deposition layer 12 but also the printed layer by providing it on the surface of the transparent vapor deposition layer 12 or the topcoat layer 22 opposite the cellophane layer 11. While ensuring transparency as a whole, the laminate film 10 (10a, 10b) may be formed with partially opaque display portions for purposes such as displaying contents, advertising, and decoration.
[0035] If problems such as moisture absorption occur due to the cellophane layer 11 being exposed on one surface of the laminate film 10 (10a, 10b), another layer may be laminated on the surface side of the cellophane layer 11. Examples of the other layer include a layer having another function such as reinforcement or moisture prevention, and the above-mentioned printed layer.
[0036] Regardless of the presence or absence of the first anchor coat layer 21, the top coat layer 22, and the second anchor coat layer 23, the total light transmittance of the entire laminate film 10 (10a, 10b) must be 80% or more, and is preferably 85% or more. If it is less than 80%, it becomes increasingly difficult to visually confirm the contents of the package. EXAMPLES
[0037] Next, the laminated film according to the present invention will be described in more detail with reference to examples in which the present invention was actually carried out. First, the raw materials used will be listed, and then the method for producing the samples will be described.
[0038] <Materials used> <Cellophane: All manufactured by Rengo Co., Ltd.> KPT#300 (thickness 20μm) Softener (glycerin) content: 13% by weight PT#300 (thickness 20μm) Softener (glycerin) content: 16~26% by weight PT#450 (thickness 30μm) Softener (glycerin) content: 23% by weight As PT#300 in Comparative Example 5, a general specification softener (glycerin) content of 13 mass % was used.
[0039] <Biodegradable resins and films> · Extrusion lamination resin (PTTMCC Biochem, BioPBS) :PBS:FZ91PM (MFR=5g / 10min, melting point=115℃) :PBSA:FD92PM (MFR=4g / 10min, melting point=84℃) ·PBS film for dry lamination (DL) : Biopearl-B, manufactured by Nichisei Chemical Co., Ltd., thickness: 20 μm Polylactic acid film : SKC, TE90C, thickness 20μm
[0040] (Example 1: PT#300 / AlOx / PBS20) For the cellophane layer, PT#300 with a softener content of 19% by mass was used as the cellophane. On one side of this, a 10 nm thick aluminum oxide (AlOx) thin film layer was formed as a transparent deposition layer by depositing aluminum as the deposition material in a vacuum deposition device using an electron beam heating method while introducing oxygen gas. On the obtained transparent deposition layer, a biodegradable resin layer was formed by extrusion lamination using PBS as a biodegradable resin with a cylinder temperature of 200 to 220°C and a T-die temperature of 250°C using a single-screw extruder (L / D=25) with a diameter of 50 mmφ and equipped with a T-die, to a thickness of 20 μm, to obtain a laminated film with a configuration corresponding to that shown in FIG.
[0041] (Example 2: PT#300 / AlOx / PBS40) A laminated film was obtained in the same manner as in Example 1, except that the thickness of the extruded PBS was changed to 40 μm.
[0042] (Example 3: PT#300 / AlOx / PBSA15) A laminated film was obtained in the same manner as in Example 1, except that PBS was changed to PBSA (thickness: 15 μm).
[0043] (Example 4: PT#450 / AlOx / PBS20) A laminated film was obtained in the same manner as in Example 1, except that the cellophane used was changed to PT#450 having a softener content of 23% by mass.
[0044] (Example 5: PT#300 / AC / AlOx / AC / PBS20) In addition to the cellophane layer, transparent vapor deposition layer, and biodegradable resin layer used in Example 1, the softener content of the cellophane was changed to 16% by mass, and the process was changed to form a first anchor coat (AC) layer and a second anchor coat (AC) layer by the following procedure, resulting in a laminated film with the configuration shown in the cross-sectional diagram of Figure 2. First, 100 parts by weight of polyester resin (Vylon 200, manufactured by Toyobo MC Co., Ltd.) and 10 parts by weight of hexamethylene diisocyanate (manufactured by Tosoh Corporation) as a curing agent were mixed to obtain a mixed resin. One side of cellophane (PT#300: softener content 16% by mass) was coated with a gravure coating method to a coating amount of 0.2 g / m after drying at 80°C. 2 This mixed resin was applied so as to form a first anchor coat layer for improving the adhesion of the transparent deposition layer. A transparent deposition layer was formed on this first anchor coat layer by the same procedure as in Example 1. Next, a urethane resin (EL510 / CAT-RT80, manufactured by Toyo-Morton Co., Ltd.) was applied on the transparent deposition layer by gravure coating so that the coating amount after drying at 80°C was 0.2 g / m 2 A second anchor coat layer for extrusion lamination was formed by applying the coating liquid so that a biodegradable resin layer was formed on the second anchor coat layer by extrusion lamination in the same manner as in Example 1 to obtain a laminated film.
[0045] (Example 6: PT#300 / AlOx / TOP / PBS20) A laminated film was obtained in the same manner as in Example 1, except that in addition to the cellophane layer, transparent vapor deposition layer, and biodegradable resin layer used in Example 1, a topcoat (TOP) layer was formed by the following procedure. First, the steps up to the formation of the transparent deposition layer were carried out in the procedure of Example 1. Next, a biodegradable polyester resin (Finart BM R Medium, manufactured by DIC Corporation) was applied onto the transparent deposition layer by gravure coating so that the coating amount after drying treatment at 80°C was 0.7 g / m 2 A top coat layer was formed by applying the solution so as to form a top coat layer. A biodegradable resin layer was formed on this top coat layer by extrusion lamination in the same manner as in Example 1 to obtain a laminated film.
[0046] (Example 7: PT#300 / AC / AlOx / TOP / AC / PBS20) In addition to the cellophane layer, first anchor coat (AC) layer, transparent vapor deposition layer, second anchor coat (AC) layer, and biodegradable resin layer used in Example 5, a top coat (TOP) layer was formed by the following procedure, to obtain a laminated film with the configuration shown in the cross-sectional view of Figure 3. First, the procedure up to the formation of the transparent deposition layer was carried out in the same manner as in Example 5. On this transparent deposition layer, a biodegradable polyester resin (Finart BM R Medium, manufactured by DIC Corporation) was applied by gravure coating to a coating amount of 0.7 g / m2 after drying at 80°C. 2 A top coat layer was formed by applying the solution as follows: A second anchor coat (AC) layer was formed on this top coat layer in the same manner as in Example 5, and a biodegradable resin layer was formed by extrusion lamination to obtain a laminated film.
[0047] (Example 8: PT#300 / AlOx / DL / PBS20 film) A transparent deposition layer was formed on the same cellophane as in Example 1 by the same procedure as in Example 1, and then a polyurethane adhesive (DIC Corporation, DiCdry LX500 / KR90S) was applied on the transparent deposition layer by gravure coating so that the coating amount after drying at 80°C was 3 g / m 3 A PBS film was dry laminated to form a biodegradable resin layer, and the resulting film was aged at 40° C. for 3 days to obtain a laminated film.
[0048] (Example 9: PT#300 / SiOx / PBS20) A laminated film was obtained by the same procedure as in Example 1, except that the softener content of the cellophane was changed to 20 mass %, and instead of the aluminum oxide thin film layer, a silicon oxide deposition material was deposited using a vacuum deposition apparatus with an electron beam heating method to form a silicon oxide (SiOx) thin film layer with a thickness of 30 nm as a transparent deposition layer.
[0049] (Comparative Example 1: Cellophane / PVDC with normal softener content: KPT#300) Polyvinylidene chloride (PVDC) latex was applied to one side of standard PT#300 cellophane, which contains 13% softener by mass, and then cured. The PVDC coating amount was 3 g / m. 2 Thus, a laminated film having the above formula was obtained.
[0050] (Comparative Example 2: Cellophane / Al) A laminated film was obtained by the same procedure as in Example 1, except that the softener content of the cellophane was changed to 20 mass %, and aluminum (Al) was evaporated as the evaporation material in a vacuum evaporation apparatus using an electron beam heating system instead of the aluminum oxide thin film layer to form an aluminum thin film layer with a thickness of 80 nm.
[0051] (Comparative example 3: PBS8 / AlOx / PT#300 / PBS8) In Example 1, after the transparent vapor deposition layer was formed, PBS was formed as a biodegradable resin layer with a thickness of 8 μm on both sides by extrusion lamination.
[0052] (Comparative Example 4: Polylactic acid film) After the transparent deposition layer was formed in Example 1, the polyurethane adhesive used in Example 8 (DIC Corporation, DIC Dry LX500 / KR90S) was applied to the transparent deposition layer by gravure coating so that the coating amount after drying at 80°C was 3 g / m 3 A PLA film was dry laminated onto the coated film to replace the biodegradable resin layer of the present invention, and the resulting film was aged at 40° C. for 3 days to obtain a laminated film.
[0053] (Comparative Example 5: Low-Softener Cellophane) An attempt was made to obtain a laminated film using the same procedure as in Example 1, except that the cellophane used was changed to cellophane with a softener content of 13% by mass, which is the general specification. However, the cellophane frequently broke when forming the transparent vapor deposition layer, and a laminated film could not be obtained.
[0054] (Comparative Example 6: Excess Softener Cellophane) An attempt was made to obtain a laminated film using the same procedure as in Example 1, except that the cellophane used was changed to cellophane with a softener content of 26% by mass. However, not only did the cellophane become sticky and contaminate the processing machine, but poor adhesion occurred and no laminated film was obtained.
[0055] [Table 1]
[0056] <Cellophane fabric softener content (%) measurement> The cellophane used was conditioned by placing it in a constant temperature and humidity chamber at 20°C x 65% RH for 8 hours or more, and the initial mass was measured. The cellophane was then dried in a hot air dryer at 105°C for 90 minutes and the mass was measured to calculate the moisture content. The cellophane was boiled in water for 15 minutes, and the difference in mass before and after drying at 105°C was calculated, and the softener content was calculated from this and the moisture value using the following formula (1). Fabric softener content (%) = (mass after hot air drying – mass after boiling and drying) / mass after boiling and drying × 100 (1)
[0057] <Total light transmittance (%) measurement> The measurement was carried out in accordance with JIS K7361 using a haze meter (Murakami Color Research Laboratory, HM-65W).
[0058] <Seal strength measurement> In accordance with JIS Z0238, the biodegradable resin layers 13 of the samples were aligned together and heat sealed at 130°C x 0.15 MPa x 1 second, then conditioned at 23°C x 50% RH for at least one day, and then a T-peel test (tensile speed: 300 mm / min) was performed using a testing machine (Shimadzu Corporation, Autograph AG-1) to measure.
[0059] <Biodegradability> For each laminate film sample, the content of biodegradable material in the mass was calculated using the following formula (2). Biodegradability (%) = mass of biodegradable material / mass of laminated film × 100 (2)
[0060] <Biodegradability in soil> A sample of the laminated film of each example was buried in soil and placed under conditions of 30°C x 50% RH. After 4 months, the weight was measured and the decomposition degree was calculated using the following formula (3) to determine biodegradability. Degradation rate (%) = 100 – (sample weight after 4 months / sample weight before test) × 100 (3) ○: Decomposition rate is 80% or more △: Decomposition rate is 30% or more and less than 80% ×: Decomposition rate is less than 30%
[0061] <Oxygen permeability> The measurements were performed under conditions of 23°C and 75% RH using an oxygen transmission rate measuring device (OX-TRAN 2 / 22, manufactured by Mocon Co., Ltd.) in accordance with JIS K7126-2.
[0062] <Result> All of the samples in the examples achieved high transparency and biodegradability, demonstrating biodegradability in soil. In addition, the oxygen barrier properties of the samples in Examples 6 and 7 were further improved by providing a topcoat layer. On the other hand, in Comparative Example 1, the seal strength was significantly poor under the same conditions as the present invention, and the PVDC layer remained even after biodegradation in soil. In Comparative Example 2, the transparency was lost because aluminum itself was vapor-deposited. In Comparative Example 3, the PBS was thin, the seal strength was poor, and the number of PBS interfaces with relatively poor smoothness on the surface of the cellophane layer increased, decreasing the transparency. In Comparative Example 4, the seal strength was poor, and the polylactic acid actually did not decompose completely in soil and remained. In Comparative Examples 5 and 6, it was difficult to produce laminated films. [Explanation of symbols]
[0063] 10, 10a, 10b Laminated film 11 Cellophane layer 12 Transparent vapor deposition layer 13 Biodegradable resin layer 21 First anchor coat layer 22 Topcoat layer 23 Second anchor coat layer
Claims
1. a cellophane layer having a content of a softener made of polyhydric alcohol of 16% by mass or more and 25% by mass or less; A transparent deposition layer made of an inorganic oxide; A biodegradable resin layer made of polybutylene succinate, polybutylene succinate adipate, or a mixture thereof; A laminated film having a total light transmittance of 80% or more, in which the transparent vapor deposition layer is disposed between the cellophane layer and the biodegradable resin layer.
2. The oxygen barrier ratio (OTR) of the transparent deposition layer is 4 cc / m 2 2. The laminated film according to claim 1, wherein the modulus is 0.05 d atm or less.
3. 3. The laminate film according to claim 1, wherein the biodegradable resin layer has a thickness of 10 μm or more and 50 μm or less.
Citation Information
Patent Citations
JP1977024608U
Biodegradable multilayer film
JP2002178456A
Biodegradable film laminate having transparent inorganic vapor deposition film layer, and bag-like article
JP2003062923A
Gas barrier base film having inorganic oxide vapor-deposition layer and protective layer
JP2006199013A